Cyclin-dependent kinase-inhibitor 1 (CDKN1A) in the squamous epithelium of the oropharynx: possible implications of molecular biology and compartmentation - Wagner, M; Klussmann, J P; Fangmann, R; Linder, Roland; Elewa, M E; Eidt, S; Rose, V M; Jungehulsing, M; Schulze, H J (Anticancer research, 2001)
The cdknlA gene encodes CDKN1A, a protein that regulates cell cycle progression, terminal differentiation, and apoptosis. Polymorphisms or loss of heterozygosity of this usually biallelically expressed gene have no major impact on carcinogenesis. The prevalence of somatic mutations in malignancies is low. Gene rearrangements involving cdknlA are scarce. CDKN1A is expressed in both premalignant and malignant lesions. While the prognostic value of nuclear CDKN1A expression is controversial, the prognostic value of its recently discovered cytoplasmic accumulation is simply unknown. CDKN1A translocates from the nucleus to the cytoplasm when cleaved by caspase-like activities during early apoptosis. The presence of cytoplasmic catabolites (e.g.: p14) might therefore indicate apoptosis. We found no correlation between nuclear and cytoplasmic anti-CDKN1A immunoreactivity in our samples of oropharyngeal squamous cell carcinoma. CDKN1A Cap20, CDKN1, CDKN1A, CDKNA1, Cip-1, Mda-6, P21, Pic1, Sdi-1, Waf-1.
Keywords: Apoptosis; Carcinoma, Squamous Cell; Cell Compartmentation; Cell Differentiation; Cyclin-Dependent Kinase Inhibitor p21; Cyclins; Genomic Imprinting; Humans; Keratinocytes; Mutation; Oropharyngeal Neoplasms; Oropharynx; Polymorphism, Genetic; Prognosis; Tumor Markers, Biological; Tumor Suppressor Protein p53